Forty Years of Labour Law Scholarship in New Zealand: A Reflection on the Contribution of Gordon Anderson - Mitchell, Richard (Victoria University of Wellington Law Review, 2019)
This special issue of the Victoria University of Wellington Law Review is published in recognition of Gordon Anderson’s outstanding contribution to the study of the academic and socio-economic policy field of labour law in New Zealand since the mid-1970s. During this period of time Gordon’s work has informed both teaching and learning in labour law scholarship and legal practice, charted the shifts in labour law policy, and examined the implications of these shifts for industrial and employment relations and human resource practices in business. This impressive output has included the publication of several full-length accounts of New Zealand labour law, incorporating background history, economic and political contexts and institutional arrangements, accompanied by analytical accounts of the general principles of individual and collective regulation. At the same time his research work, and his extensive engagement with labour lawyers internationally, has considerably expanded the international understanding and interest in New Zealand’s labour law system, drawing it more immediately and closely into comparison with other national systems and sets of laws.